2018
DOI: 10.3897/rrpharmacology.4.25529
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction: comparative evaluation of ultrasound dopplerography, laser dopplerflowmetry and direct monitoring of arterial pressure for conducting pharmacological tests in rats

Abstract: Introduction: The importance of the problem of endothelial dysfunction makes it essential to improve approaches to its evaluation. Due to the high diagnostic potential of ultrasound dopplerography, this method is promising in the study of endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Left ventricular noncompaction (LVNC) is a form of CHD caused by arrested compaction, which usually affects both ventricles and is characterized by excessive trabeculation with deep intertrabecular recesses and a thin compact myocardium. Typical LVNC complications are systemic embolic events, ventricular arrhythmias and heart failure [38,39]. Homozygous Slc39a8null mice embryos do not survive embryogenesis and exhibit an LVNC-similar cardiac phenotype.…”
Section: Zn 2+ In Heart Developmentmentioning
confidence: 99%
“…Left ventricular noncompaction (LVNC) is a form of CHD caused by arrested compaction, which usually affects both ventricles and is characterized by excessive trabeculation with deep intertrabecular recesses and a thin compact myocardium. Typical LVNC complications are systemic embolic events, ventricular arrhythmias and heart failure [38,39]. Homozygous Slc39a8null mice embryos do not survive embryogenesis and exhibit an LVNC-similar cardiac phenotype.…”
Section: Zn 2+ In Heart Developmentmentioning
confidence: 99%
“…Structural changes in diabetic myocardium are usually assessed by non-invasive reliable and reproducible techniques (such as magnetic resonance imaging and echocardiography), with myocardial fibrosis and hypertrophy as the main hallmarks of DCM [ 12 , 13 ]. While MRI has better sensitivity and capability to provide a more detailed image, it is also more expensive, thus, not so widely used as echocardiography––the main diagnostic tool for the early DCM detection [ 14 , 15 ].…”
Section: Structural and Functional Alterations In Dcmmentioning
confidence: 99%
“…Factors affecting endothelial function (for example, insulin) capable of metabolic parameters of bone tissue to cause an improvement of coronary microvascular function in individuals with chronic kidney disease remains unclear. Usually, patients with developing ASCVD also have risk factors for cardiovascular disease, including albuminuria and general growth in inflammatory markers [ 86 , 87 , 88 ]. In their study, Rein et al showed that the existence of albuminuria is linked with a higher probability of detecting significant coronary artery stenosis (≥ 50%) during angiography.…”
Section: Pathophysiologic Considerations Of Ascvd In Ckdmentioning
confidence: 99%